Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1017/s0144686x18001320
|View full text |Cite
|
Sign up to set email alerts
|

Spousal care-giving arrangements in Europe. The role of gender, socio-economic status and the welfare state

Abstract: Spouses (and partners) are the most important source of care in old age. Informal care for frail spouses is provided by both sexes and across all socio-economic backgrounds and welfare policy contexts. There are, however, interesting differences as to whether spouses care alone, receive informal support from other family members or formal support from professional helpers, or outsource the care of their spouse completely. The present article contributes to the literature by differentiating between solo spousal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 48 publications
3
63
0
3
Order By: Relevance
“…Informal or family care-givers are usually a family member, often a spouse or friend, generally female, who assumes the overall caring responsibility for a person experiencing daily difficulties due to a debilitating condition, physical, cognitive or emotional, including dementia (Brodaty and Donkin, 2009; Alzheimer's Society, 2015; Carers Trust, 2015; Bertogg and Strauss, 2018). Informal care-giving will generally have a relational dimension, and whilst often the spouse is the main carer, other family members often provide a significant contribution (McDonnell and Ryan, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Informal or family care-givers are usually a family member, often a spouse or friend, generally female, who assumes the overall caring responsibility for a person experiencing daily difficulties due to a debilitating condition, physical, cognitive or emotional, including dementia (Brodaty and Donkin, 2009; Alzheimer's Society, 2015; Carers Trust, 2015; Bertogg and Strauss, 2018). Informal care-giving will generally have a relational dimension, and whilst often the spouse is the main carer, other family members often provide a significant contribution (McDonnell and Ryan, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Another explanation for their unaided caring may be that their partner is not being offered services because they are lower priority given their age and non-malignant conditions [17]. More research is needed in this area, including the views of service providers [75] as well as from a gendered perspective given wider evidence that indicates men tend to receive more formal and informal support whilst caring than women [30,108].…”
Section: Discussion and Implications For Research Policy And Practicementioning
confidence: 99%
“…As Table 1 shows, those recruited fell into all of these categories. The categories were chosen because the literature suggested that these factors were important for influencing experiences of caring: we referred above to the relevance of employment and spatial distribution of families, and the salience of gender has been widely considered (Bertogg and Strauss, 2020). Table 1 provides an overview of the study participants.…”
Section: Methodsmentioning
confidence: 99%